Physico-spectrochemical characterization and antibacterial property of humic acid (HA) from Sta. Barbara artesian well-water. - Valera, Jessebel Patchicoy (University of the Philippines Visayas, 2016)
The coloration of Sta. barbara artesian well-water is due to humic acid (HA). HA is a complex organic compound formed in soils, sediments, and natural waters by biochemical and chemical reactions during the decay and transformation of plant and microbial remains. It was extracted through acid precipitation, centrifugation, and freeze-drying method, consecutively and was found to be present at 76.50 (4.48) mg/l. Scanning electron micrographs with 50x up to 35,000x magnification reveal that HA is an amorphous organic compound having no definite shapes and sizes. HA is seen as chipped granules tending to aggrefate to each other and with some crystalline salts bound to its structure.